Design de triggers emocionais para experiências gastronômicas - Akiyoshi, Ricardo Yudi (Universidade do Vale do Rio dos Sinos, 2012)
This dissertation presents the study of emotional triggers for food experiences in a Design context. More specifically, we brought the fields of Strategic Design, Design Emotion, Design for Experiences and Food Design together. Our object of research consisted in dining experiences and other variables related to food and design services. The startup point of this study was the socioeconomic changes, consumer behavior and how one could maintain himself competitive in the current market. One way to stay competitive could be developing better products and services through innovative experiences. These types of experiences could be achieved developing emotional stimuli that could improve the flow and overall quality of a certain experience. In order to achieve this, the study collected data throughout a series of two experiments (experiment I and II) and a survey to answer the following main aspect: evaluation of emotional behavior in food experiences due to the manipulation of tangible and intangible triggers. We will conclude that it is possible to condition an experience and intensify positive emotions due to the manipulation of certain variables. The resulting emotions will always be, however, conditioned to the users? interpretation of the experience. We will suggest in the end of our research that one of the roles the Design field of study could take part in, is the articulation and design of projects that enhance the overall quality of an experience and well being of the user. To our future research we pointed out the need for more experiments; the careful study regarding the lifespan and chronology of user experiences and deepen our thoughts in themes like meaning and identity values regarding food experiences.
Keywords: Design; Design para experiências; Design emocional; Gastronomia; Triggers emocionais; Experience design; Emotional design; Gastronomy; Emotional triggers; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial